Politics and feminism: An introduction - Arneil, Barbara (Blackwell, 1999)
This book addresses the question of gender and feminism in western political theory and practise. It provides students with both the theoretical and historical underpinnings of women's exclusion from politics, and the feminist response to this exclusion.
Keywords: amériques; approches et analyses; cours; discipline; discriminations; europe; fem1000; histoire et politique; inégalités; occident; premier cycle; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; théories politiques

With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Mémoires d'une bataille inachevée : la lutte pour l'avortement au Québec, 1970-1992 - Desmarais, Louise (Éditions Trait d'union, 1999)
Chronique des événements entourant la lutte pour l'avortement libre et gratuit, l'une des plus importantes revendications du mouvement féministe québécois. Les différents groupes qui ont mené le combat, leurs discours et la place de leurs actions dans la dynamique des relations qu'ils entretenaient avec les gouvernements et le mouvement anti-avortement. Etude appuyée sur une solide documentation.
Section: 441 pages ; 23 cm
Keywords: 1800-1899; 1900-1999; amérique du nord; amériques; approches et analyses; avortement; canada; droits des femmes*; histoire des femmes*; histoire et politique; justice reproductive; militance; patriarcat; périodes historiques; québec; régions géographiques; systèmes d'oppressions; thématiques

Queer theory: Under construction - Dilley, Patrick (International Journal of Qualitative Studies in Education, 1999)
This article outlines how the concepts of queer and queer theory have been applied to qualitative studies. The multiple definitions of queer are examined, to foster an understanding of the positions from which theorists have utilized the concept to examine a number of disciplines. The advancement of the tenets of queer theory is outlined chronologically, to display the evolution of the theory through intradisciplinary applications. The body of qualitative works utilizing queer theory is categorized (language, literature, and arts; history; life histories / life stories; and queer theory as praxis) and juxtaposed. In addition, efforts to define and enact a "queer pedagogy" are analyzed. Suggestions for further application of queer theory in education, ethnography, and qualitative studies conclude the article.
Keywords: approches et analyses; discipline; discours dominant; ethnographie; histoire et politique; hétérosexisme; pédagogie; pédagogie queer; queer; ressource en ligne; sciences de l'éducation; systèmes d'oppressions; thématiques; éducation; étude qualitative

Le mariage des homosexuels : politique comparee des normes franco-americaines - Fassin, E. (FRENCH POLITICS AND SOCIETY, 1999)
Keywords: analyse comparée; cours; his4860; histoire et politique; premier cycle; régions géographiques; thématiques

Une organisation maternaliste au Québec la Fédération nationale Saint-Jean-Baptiste et la bataille pour le vote des femmes - Hébert, Karine (Revue d'histoire de l'Amérique française, 1999)
Cet article présente, à la lumière des développements récents de l'historiographie féministe, une nouvelle interprétation de la Fédération nationale Saint-Jean-Baptiste. Cette réinterprétation se base sur un concept assez nouveau: le maternalisme, défini comme une catégorie d'analyse utilisée pour qualifier les mouvements de femmes chez qui la maternité constituait le point central de l'idéologie et de l'argumentation. Nous examinons, entre autres, le modèle féminin véhiculé par la FNSJB pour constater qu'il correspondait au modèle traditionnel de « la femme », celui qui effectuait une équation entre la femme et la mère. La maternité n'était toutefois pas perçue par la FNSJB comme une fonction limitative, mais bien comme une ouverture vers la société. Elle a donc dû redéfinir les frontières entre les sphères privée et publique pour permettre aux femmes de transgresser celles du foyer et faire bénéficier la société de leur influence maternelle. Le cadre d'analyse élaboré dans la première partie est ensuite appliqué à un cas concret de revendication: la bataille pour le vote des femmes.
https://www.erudit.org/en/journals/haf/1999-v52-n3-haf219/005467ar/
Keywords: 1900-1909; 1900-1999; 1910-1919; amériques; approches et analyses; canada; changement social; corps; cours; droit de vote; fem1000; histoire des femmes*; histoire et politique; maternité; militance; mouvements féministes; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Femmes du siècle - Institut de recherches et d'études féministes (FéminÉtudes, 1999)
Cette publication de 1999 porte sur l’histoire des féminismes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Disponible en libre accès : https://iref.uqam.ca/feminetudes/vol-4-no-1-1999-femmes-du-siecle/
Keywords: 1900-1999; 1990-1999; amériques; discipline; féminétudes; histoire; histoire des femmes*; histoire et politique; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; thématiques

Théoriser le genre : l'héritage de Beauvoir - Jackson, Stevi (Nouvelles Questions Féministes, 1999)
En déclarant qu' "on ne naît pas femme, on le devient", Simone de Beauvoir a posé les fondements d'une conception féministe du genre. L'analyse développée dans Le Deuxième sexe a anticipé la distinction ultérieure entre sexe et genre, et a également soulevé certains problèmes liés à cette distinction. Plutôt que l'oeuvre même de Beauvoir, ce sont les discussions récentes autour de la distinction sexe/genre qui font l'objet de cet article. Plus particulièrement, j'examine la manière dont les féministes matérialistes françaises, avec qui Beauvoir elle-même a travaillé, ont fait fructifier son héritage. En affirmant que le "sexe" est un phénomène tout aussi social que le "genre", ces féministes ont maintenu une tradition anti-essentialiste fondamentalement opposée aux perspectives "différentialistes" si souvent associées à la construction anglophone du "French feminism". Je confronte la contribution de ces féministes, notamment Christine Delphy et Monique Wittig, aux conceptions féministes du genre, avec l'approche plus déconstructive associée à des théoriciennes comme Judith Butler. Ce faisant, je plaide pour une analyse matérialiste du genre et pour une vision d'un monde sans genre plutôt que d'un monde avec de multiples genres. In claiming that 'one is not born, but rather becomes, a woman', Simone de Beauvoir laid the foundations for a feminist understanding of gender. The analysis developed in The Second Sex anticipated the later distinction between sex and gender, and also evinced some of the problems associated with that distinction. It is these more recent discussions of the sex/gender distinction which are the focus of this paper, rather than Beauvoir's work itself. More specifically, I consider the ways in which French materialist feminists, with whom Beauvoir herself worked, carry forward her legacy. In arguing that ' sex' is as much a social phenomenon as 'gender', these feminists have kept alive an anti-essentialist tradition which is fundamentally opposed to the 'difference' perspectives so often associated with the anglophone construction of ' French Feminism'. I compare the contribution that these feminists, especially Christine Delphy and Monique Wittig, have made to feminist understandings of gender with the more deconstructive approach associated with thinkers such as Judith Butler. In so doing I argue the case for a materialist analysis of gender and for a vision of a world without gender rather than a world with many genders.
https://www.jstor.org/stable/40619720
Keywords: 1900-1999; approches et analyses; cours; discipline; fem1000; france; féminisme matérialiste; genre; histoire; histoire et politique; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; thématiques; théories féministes

Repenser l’État: Nouvelles perspectives féministes - Masson, Dominique (Recherches féministes, 1999)
Depuis déjà une dizaine d'années, les limites des théories féministes classiques sur l'État sont soulignées par de nouvelles perspectives féministes. Leurs reconceptualisations offrent une voie médiane entre le volontarisme des approches libérales et le déterminisme des conceptions plus structurelles. Ancrées dans les notions de luttes politiques et de rapports de forces, celles-ci réorientent l'analyse de «l'État » vers celle de la spécificité des formes étatiques. Elles redonnent également aux luttes des femmes et aux processus de représentation politique une portée analytique et stratégique de même qu'elles permettent une meilleure prise sur la relation entre l'État et l'action politique des femmes.
Disponible en ligne: http://dx.doi.org/10.7202/058018ar
Keywords: cours; discipline; histoire et politique; pol4102; pol5480; premier cycle; ressource en ligne; science politique; science politique et droit; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Routledge, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

A critique of postcolonial reason: Toward a history of the vanishing present - Spivak, Gayatri Chakravorty (Harvard University Press., 1999)
Are the “culture wars” over? When did they begin? What is their relationship to gender struggle and the dynamics of class? In her first full treatment of postcolonial studies, a field that she helped define, Gayatri Chakravorty Spivak, one of the world’s foremost literary theorists, poses these questions from within the postcolonial enclave. “We cannot merely continue to act out the part of Caliban,” Spivak writes; and her book is an attempt to understand and describe a more responsible role for the postcolonial critic. A Critique of Postcolonial Reason tracks the figure of the “native informant” through various cultural practices—philosophy, history, literature—to suggest that it emerges as the metropolitan hybrid. The book addresses feminists, philosophers, critics, and interventionist intellectuals, as they unite and divide. It ranges from Kant’s analytic of the sublime to child labor in Bangladesh. Throughout, the notion of a Third World interloper as the pure victim of a colonialist oppressor emerges as sharply suspect: the mud we sling at certain seemingly overbearing ancestors such as Marx and Kant may be the very ground we stand on. A major critical work, Spivak’s book redefines and repositions the postcolonial critic, leading her through transnational cultural studies into considerations of globality.
Keywords: 1900-1999; 1980-1989; arts; cours; discipline; fem1000; histoire; histoire et politique; international; premier cycle; périodes historiques; sciences humaines; sofia; thématiques; théories féministes; études culturelles; études littéraires; études postcoloniales